RELATIONSHIP PARENTING PARENTS OF THE LEARNING ACHIEVEMENT OF CHILDREN IN PRIMARY SCHOOLS SENAGARI SARIAK LAWEH KEC. AKABILURU KABUPATEN LIMA PULUH KOTA (Correlation Studies in The School of Inclusive Education Provider)”. - Rahmita Filiyanti (Universitas Negeri Padang, 2015)
This research is motivated their students underachieving whose value does not reach KKM. The school has attempted to implement a good learning method, even doing cooperate with the parents. However, students often do not do homework, play directly after school, even they do not replace the school uniforms. Therefore, researcher wanted to know why this happens, because the learning process not only at school but also at home and is related to the parenting of parents of learners. Researcher want to use a method that is both descriptive correlational with the aim to see the relationship parenting parents of the learning achievement of children in primary schools Senagari Sariak Laweh Kec. Akabiluru Kabupaten Lima Puluh Kota, using the techniques of data collection in the form of a questionnaire, while the data source is students and teachers. Data obtained from the results of research in which the calculation results obtained sig. smaller dai sig. alpha (0.000 <0.05). So the hypothesis (Ho) as stated above is rejected, otherwise the alternative hypothesis (Ha) is accepted. It is concluded there is a significant relationship between parenting parents with learning achievement of children in primary school Senagari Sariak Laweh Kec. Akabiluru Kabupaten Lima Puluh Kota.keywords; parenting parents; learning achievement; child learningdisabilities; school organiziers inclusive education